2018
DOI: 10.1007/s00392-018-1405-1
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete echocardiographic recovery at 6 months predicts long-term sequelae after intermediate-risk pulmonary embolism. A post-hoc analysis of the Pulmonary Embolism Thrombolysis (PEITHO) trial

Abstract: Introduction Symptoms and functional limitation are frequently reported by survivors of acute pulmonary embolism (PE). However, current guidelines provide no specific recommendations on which patients should be followed after acute PE, when follow-up should be performed, and which tests it should include. Definition and classification of late PE sequelae are evolving, and their predictors remain to be determined. Methods In a post hoc analysis of the Pulmonary Embolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 21 publications
2
38
0
Order By: Relevance
“…Sustained echocardiographic improvement seems to be important for preventing the post-PE syndrome by enabling more complete functional recovery. 32 Kahn et al 8 examined 100 patients at 1 and 12 months after PE. Nearly half had exercise limitation and echocardiographic abnormalities at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Sustained echocardiographic improvement seems to be important for preventing the post-PE syndrome by enabling more complete functional recovery. 32 Kahn et al 8 examined 100 patients at 1 and 12 months after PE. Nearly half had exercise limitation and echocardiographic abnormalities at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…26 Additionally, a further post hoc analysis of the PEITHO trial suggested that 13% of those with intermediate risk PE had either post-PE syndrome or CTEPH when combining both echocardiographic findings and NYHA functional classification. 27 However, direct comparison of the functional and radiological measures in these trials should be performed with caution due to differences in the definitions of outcome measures. Our study demonstrates that initial risk stratification is useful in predicting which patients with acute PE may be at risk of developing RV dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Further diagnostic evaluation e may be considered in asymptomatic patients with risk factors for CTEPH f [447][448][449]478]. C IIb CPET: cardiopulmonary exercise testing; CT: computed tomography; CTEPH: chronic thromboembolic pulmonary hypertension; PE: pulmonary embolism; PH: pulmonary hypertension; V/Q: ventilation/perfusion (lung scintigraphy).…”
Section: Iiamentioning
confidence: 99%